Exploring Brain Gain Potential: Overseas Work Experience and Return Migrant Income in Indonesia - Feisal Sinaga; Padang Wicaksono (Universitas Negeri Malang, 2023)
This study aims to analyze the effect of overseas work experience and education level on the income of return Indonesian Migrant Workers (purna PMI) compared to non-PMI. The unit of analysis used is workers aged 20-40 years who are relatively young and have long career paths. The data used is Sakernas of August 2021, and the analytical method used is the Two Step Heckman Method to overcome selectivity bias problems. The results show that the achievement of human capital purna PMI is not better than non-PMI, where most purna PMI have low education, and only a few are highly educated. The results of the inferential analysis show that only highly educated purna PMI earn a higher income of 19.5% compared to non-PMI (earnings premium), reflecting the brain gain effect. In contrast, purna PMI with low education has a lower income of 9.01% (earnings penalty) compared to non-PMI with the same level of education.